Labor Market Institutions, Mobility, and Dualization in the Nordic Countries - Svalund, Jørgen (Nordic Journal of Working Life Studies, 2013)
Comparing the Nordic countries, this article examines different combinations of permanent and temporary employment protection legislation, and whether such differences are reflected in patterns of labor market transitions. We find higher levels of transitions from unemployment to temporary contracts in Sweden and Finland, with lax regulation of temporary contracts and strict regulation of permanent contracts. Further, temporary employees are integrated into permanent contracts in countries with lax (Denmark) or strict (Norway) regulation of permanent contracts, while this is not the case in Finland and Sweden. For these countries, the study indicates a certain degree of labor market duality, with low mobility from temporary to permanent employment contracts.